OEE improvement through reducing start up duration using lean six sigma methodology in manufacturing - Khisbulloh, Wijaya; Yudoko, Gatot (Goodwood Publishing, 2024)
Purpose: This research focuses on improve OEE by reducing start-up duration using Lean Six Sigma methodology. By applying Lean Six Sigma tools and techniques, manufacturers can systematically analyse the start-up process, identify root causes of delays, and implement targeted improvements. Methodology/approach: The research presented in this journal comprises a comprehensive study conducted within a manufacturing setting to demonstrate the effectiveness of the proposed approach. The study involves the collection and analysis of data related to start-up durations, downtime reasons, and other relevant parameters. Through the DMAIC (Define, Measure, Analyse, Improve, Control) framework of Lean Six Sigma, the root causes of prolonged start-up durations are identified and addressed. Results: The results demonstrate the potential for significant OEE improvements through the elimination of bottlenecks and inefficiencies in the start-up process. Manufacturers can leverage the findings of this research to develop strategies that enhance operational effectiveness, increase production output, and ultimately drive competitive advantage in the dynamic landscape of modern manufacturing. Conclusions: Lean Six Sigma, through the DMAIC approach, effectively reduces start-up time and improves OEE. Addressing root causes leads to better equipment utilization and increased productivity. Limitations: This research limitation is only for manufacturing or production area that having OEE as their main key performance indicator. Contribution: This research will contribute to the manufacturing operation excellency.